The Effect of Service Quality, Campus Ecology, and Self-Efficacy on Students’ Satisfaction in Anaa Specialist Education Program, Diponegoro University Semarang - Hartanto, Fitri; Rusdarti, Rusdarti; Yanto, Heri; Purwanti, Asri (Universitas Negeri Semarang, 2019)
Student satisfaction is an important indicator of the quality of higher education and is a measure of the service quality of its customers. Student satisfaction with their educational institutions also depends on the situation of the campus environment created for the convenience of the students. The main objective of this study is to obtain empirical evidence regarding the impact of service quality, campus ecology, and self-efficacy on the satisfaction level of the students of ANAA Specialist Education Program, Diponegoro University (PPSA UNDIP) Semarang. The population of this study was 125 specialist students of UNDIP and the students were chosen to be selected as samples using random sampling techniques. Data was drawn using a questionnaire; the data were analyzed using the SPSS and the Lisrel 8.54 program. The results of the study show that (1) service quality significantly affected self-efficacy and student satisfaction; (2) campus ecology has a significant effect on self-efficacy of 75.69% and on student satisfaction by 43.56%; (3) service quality and campus ecology together have a significant effect on student self-efficacy; (4) service quality, campus ecology, and self-efficacy together also have a significant effect on the satisfaction of the students of PPDSA UNDIP Semarang. Service quality and campus ecology are antecedent variables of self-efficacy and the three variables are determinants of the satisfaction of the students at the institution.